The contribution of reticular basement membrane proteins to basal airway epithelial attachment, spreading and barrier formation: implications for airway remodeling in asthma - Hsieh, Aileen; Yang, Chen Xi; Al-Fouadi, May; Nwozor, Kingsley Okechukwu; Osei, Emmanuel Twumasi; Hackett, Tillie-Louise (Frontiers in Medicine, 2023)
Rationale In the healthy lung, the pseudostratified conducting airway epithelium is anchored to the reticular basement membrane (RBM) via hemidesmosome junction complexes formed between basal cells and the extracellular matrix (ECM). The RBM within the healthy lung is composed of the ECM proteins laminin and collagen-IV. In patients with asthma, the RBM is remodeled with collagen-I, -III and fibronectin deposition. The goal of this study was to assess the effect of RBM ECM proteins on basal airway epithelial cell attachment, spreading and barrier formation using real-time electrical cell-substrate impedance sensing (ECIS). Methods ECIS 8-well arrays were coated with 50 μg/mL of fibronectin, collagen-I, collagen-III, collagen-IV, or laminin and compared to bovine serum albumin (BSA) or uncoated controls. The airway epithelial cell line (1HAEo-) was seeded 40, 50, 60, and 70 k cells/well and continuously monitored over 70 h to assess cell attachment, spreading and barrier formation using high (64 k Hz) and low (500 Hz) frequency resistance and capacitance. Data were analyzed using a one-phase decay model from which half-life (time cells cover half of the electrode area) and rate-constant (cell-spreading rate/h) were determined and a generalized additive mixed effect model (GAMM) was used to assess ECM proteins over the entire experiment. Results High-frequency (64 kHz) capacitance measures demonstrated the half-life for 1HAEo-cells to attach was fastest when grown on fibronectin (6.5 h), followed by collagen-I (7.2 h) and collagen-III (8.1 h), compared to collagen-IV (11.3 h), then laminin (13.2 h) compared to BSA (12.4 h) and uncoated (13.9 h) controls. High-frequency (64 kHz) resistance measures demonstrated that the rate of 1HAEo- cell spreading was significantly faster on fibronectin and collagen-I compared to collagen-III, collagen-IV, laminin, BSA and the uncoated control. Low-frequency (500 Hz) resistance measures demonstrated that 1HAEo-cells formed a functional barrier fastest when grown on fibronectin and collagen-I, compared to the other ECM conditions. Lastly, the distance of 1HAEo-cells from the ECM substrates was the smallest when grown on fibronectin reflecting high cell-matrix adhesion. Conclusion Airway epithelial cells attach, spread and form a barrier fastest on fibronectin, and collagen-I and these reticular basement membrane ECM proteins may play a protective role in preserving the epithelial barrier during airway remodeling in asthma.